Effect of biopolymer composition on the viability of Trichoderma sp. as maize-seed coating - Ahmad Arsyadmunir; Gita Pawana; Kaswan Badami; Nuriatus Sholikhah; Yenny Wuryandari (Agrovigor, 2023)
Trichoderma spp., is a fungus with the ability to control disease and promote plant growth. The mechanism is through the activity of microparasites, antimicrobial secondary metabolites, phytohormones and mobilization of plant nutrients for plant growth and production. The purpose of this study was to examine the biopolymer composition as a seedcoating formula on corn seeds with Trichoderma as the active ingredient, namely to obtain a biopolymer composition that is able to maintain viability and inactivate Trichoderma during storage. Completely randomized design was used with a single treatment factor for the composition of the formula, i.e.; K1 is control 1 (suspension of conidia Trichoderma sp.); K2 is xanthan gum 2.5% + Na alginate 2.5% + conidia suspension Trichoderma sp. + talk; K3 is xanthan gum 5% + Na alginate 5% + conidia suspension Trichoderma sp. + talk; K4 is xanthan gum 2.5% + CMC 2.5% + conidia suspension Trichoderma sp. + talk; K5 is xanthan gum 5% + CMC 5% + conidia suspension Trichoderma sp. + talk; K6 is Na alginate 2.5% + CMC 2.5% + Trichoderma sp. conidia suspension. + talk; K7 is Na alginate 5% + CMC 5% + conidia suspension Trichoderma sp. + talk; K8 is control 2 (suspension of conidia Trichoderma sp. + Talc). The results obtained showed that the composition of the seedcoating formula consisting of 5% xanthan gum + 5% Na alginate + Trichoderma conidia suspension + talc up to 60 days after application of seedcoting on seeds could inactivate Trichoderma reproduction, but could not suppress the decrease in viability.